Perbandingan Pendapatan Pajak Daerah dengan Tingkat Kesejahteraan Masyarakat Jakarta Utara - Aulia Khoirun Nisaa'; Daffa Eka Saputra; Eva Hany Fanida; Revienda Anita Fitrie (Indo-MathEdu Intellectuals Journal, 2026)
This study is motivated by the need for Islamic education to respond to the diverse characteristics of learners and the demands of independent learning in the contemporary era. Until now, learning practices have tended to focus on a single specific approach, and thus have not fully accommodated the development of learners’ learning autonomy. This study aims to analyse learning designs based on the principles of pedagogy, andragogy, and heutagogy, as well as their relevance within the context of Islamic education. The research employs a qualitative approach through a systematic literature review of reputable journal articles, academic books, and relevant conference proceedings, with data analysis conducted using thematic analysis. The results indicate that pedagogy, andragogy, and heutagogy form a learning continuum representing a shift from teacher-centred learning towards learner-determined learning. These three approaches have fundamental differences regarding the roles of learners and educators, the structure of learning, learning orientation, and evaluation strategies; however, they are complementary within Islamic education. The implications of this research emphasise the need for an integrated learning design that is adaptive to learners’ developmental levels and autonomy, and supports the strengthening of lifelong learning in the management of Islamic education